Processos de estigmatização, atribuição de causalidade e resiliência em famílias no contexto da dependência química - Silva, Franciane Fonseca Teixeira (2023)
This thesis aims to analyze the processes of stigmatization, attribution of causality and resilience by family members of people in chemical dependence. A cross-sectional, exploratory and descriptive study was conducted, with quantitative design and non-probabilistic (convenience) and dependent (the same sample for all studies), accounting for 111 participants aged between 18 and 70 years, most of them female, married with high schooling. The collection took place via online electronic form, according to the resolutions of the Current Ethics Council and stored on the internet server. The results were organized into four articles. The first article aimed to identify the causes attributed by the family member to the chemical dependence of the family member, considering their location/internality (internal or external to the individual), stability (stable/instable) and controllability. Based on the Attributeal Model of Action (Weiner, 1972), he used the Locus Scale of Parental Control in Health. The results indicated instability (detoxification treatment + relapse) for 52% of the chemical dependents being attributed external control location, in this case to the field of medicine, specifically to the hospital, physician and psychiatrist or to fatalism. The second article aimed to identify the perception of the stigma suffered, as well as interpersonal rejection linked to stigma due to a chemicaldependent family member. Based on Goffman's studies (1988), the Perceived Stigma Scale (Soares, 2011) was used as an instrument. The results indicate the presence of moderate internalized stigma, with the highest means and correlation in the factors Stereotype Approval followed by Resistance to Stigma. No statistically significant difference was found between the perception of stigma in relation to the typification of the psychoactive substance. Thus, it is confirmed that the perception of stigma directed at their group of belonging results in negative self-perceptions when taking for themselves the stereotypes and social stigmas about the chemical dependent family member. The third article, based on the Model of Resilience, Stress, Adjustment and Family Adaptation (McCubbin & McCubbin, 1993), aimed to verify the capacity of family resilience considering coherence, flexibility, involvement and social support. The Resilience, Stress, Adjustment and Family Adaptation Questionnaire was used, which allowed the evaluation of how the family responds to stress and crisis situations. The fourth article aimed to verify the correlation between the variables related to Attribution of Causality, Perception of Stigma and the factors of Family Resilience. For this purpose, descriptive and multivariate statistics were used to correlate and analyze the variables identified in previous studies. It is expected to contribute to the construction of therapeutic interventions from the perspective of the family of the chemical addict.